The Pendleton field guide to campfire cooking - Keats, Sarah; Bro, Lindsey (The Pendleton field guide series, 2022)
"Brimming with Pendleton's signature patterns and timeless wisdom, this handsome book is a wonderful companion for families and friends who love spending time in nature. Discover expert tips on how to prep ingredients ahead of time, easily transport supplies, and cook over an open fire or camping stove." -- Amazon.com.